(untitled) (Eurasian Journal of Philology Science and Education, 2016)
The world of business is absolutely special world, with the specific rules, terminology, it is proper to it the own specific discourse – a business discourse which is object of research of business linguistics is considered in the article. Nevertheless this problem was studied in the English-speaking environment in 1990, and in Russian research was begun in 2000, the Kazakh linguists only started investigating. Works of foreign scientists about business linguistics, the review of the main directions of its research also define basic approaches to its analysis. Definitions of the term «business discourse» and «practical discourse» differ, the functional typology of a business discourse is classified. Authors draw a conclusion that an integrated approach of research of the following aspects: research of business linguistics in applied linguistics, the main directions of business communication, the oral, written and technically mediated business communication, its typology and genre classification, professional sublanguages of a business area (for example, bank, exchange, accounting, administrative, production, etc.), the business lexicography, business terminology, document science (document linguistics), etc. gives an effective result.